2021
DOI: 10.1177/17407745211028588
|View full text |Cite
|
Sign up to set email alerts
|

Covariate adjustment in subgroup analyses of randomized clinical trials: A propensity score approach

Abstract: Background: Subgroup analyses are frequently conducted in randomized clinical trials to assess evidence of heterogeneous treatment effect across patient subpopulations. Although randomization balances covariates within subgroups in expectation, chance imbalance may be amplified in small subgroups and adversely impact the precision of subgroup analyses. Covariate adjustment in overall analysis of randomized clinical trial is often conducted, via either analysis of covariance or propensity score weighting, but c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 38 publications
0
5
0
Order By: Relevance
“…The current study was focused on the use of different sets of weights to estimate the effect of treatment in observational (or nonrandomized) studies. Both Zeng et al and Yang et al described the use of overlap weights in randomized controlled trials 29,30 . The use of weighting allows the analyst to reduce the effects of residual imbalance in measured baseline covariates between treatment groups.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The current study was focused on the use of different sets of weights to estimate the effect of treatment in observational (or nonrandomized) studies. Both Zeng et al and Yang et al described the use of overlap weights in randomized controlled trials 29,30 . The use of weighting allows the analyst to reduce the effects of residual imbalance in measured baseline covariates between treatment groups.…”
Section: Discussionmentioning
confidence: 99%
“…Both Zeng et al and Yang et al described the use of overlap weights in randomized controlled trials. 29,30 The use of weighting allows the analyst to reduce the effects of residual imbalance in measured baseline covariates between treatment groups.…”
Section: F I G U R E 7 Case Study-overlap and Balance Diagnosticsmentioning
confidence: 99%
“…Furthermore, we used several PS-based models to correct for the imbalanced case numbers and estimated the risk of mortality under different model settings, including overlap weighting, average treatment effect on the treated (ATT), and inverse probability treatment weighting (IPTW). For example, the overlap weighting model added weights to subjects on the basis of demographic features between CHM users and nonusers, including age, gender, lifestyles, comorbidities, initial treatments, and medications [35]. These covariates were used to generate the probability of using CHM as PS, and the PS was assigned as a weight to CHM nonusers while 1 − PS was assigned to CHM users [36].…”
Section: Discussionmentioning
confidence: 99%
“…OW completely removes imbalance, attaining the same semiparametric variance lower bound as the ANCOVA/IPTW estimator and consistently outperforming IPTW in finite samples. Yang, Li, Thomas, and Li (2021) extended OW to subgroup analyses and compared OW to a full-interaction ANCOVA-S model on the overall sample with baseline covariates, treatment indicator and their interactions with the subgroup variables. They showed that ANCOVA-S estimator is as efficient as weighting methods with full interaction, when the ANCOVA model is correctly specified, while OW estimator with propensity score estimated from a full-interaction model on the treatment indicator outperforms ANCOVA-S under small subgroup sample size, and/or when the ANCOVA is misspecified.…”
Section: Propensity Scores In Outcome Analysismentioning
confidence: 99%